Hypertriglyceridaemia in extremely preterm infants receiving parenteral lipid emulsions - Ruth Sinclair; Tim Schindler; Kei Lui; Srinivas Bolisetty (BMC, 2018)
Abstract Background Lipid emulsions (LE) are routinely administered as part of parenteral nutrition in neonates. There is a wide variation in clinical practice of plasma triglyceride monitoring during LE therapy. Our aim was to evaluate the incidence of hypertriglyceridaemia (Plasma triglyceride > 2.8 mmol/L) and its association with mortality and major morbidities in extremely preterm infants on parenteral nutrition. Methods A retrospective review of 195 infants < 29 weeks gestation. Lipid emulsion was commenced at 1 g/kg/day soon after birth and increased by 1 g/kg daily up to 3 g/kg/day and continued until the infant was on at least 120 ml/kg/day of enteral feeds. Plasma triglyceride concentrations were measured at each increment and the lipid emulsion dosage was adjusted to keep plasma triglyceride concentrations ≤2.8 mmol/L. Results Hypertriglyceridemia was noted in 38 neonates (32.5% in 23-25 weeks and 16.1% in 26-28 weeks). Severe hypertriglyceridemia (> 4.5 mmol/L) was noted in 11 infants (10.0% in 23-25 weeks and 4.5% in 26-28 weeks). Hypertriglyceridemia was associated with an increase in mortality (unadjusted OR 3.5; 95% CI 1.13-10.76; 0.033) and severe retinopathy of prematurity (unadjusted OR 4.06; 95% CI 1.73-9.59; 0.002) on univariate analysis. However, this association became non-significant in multivariate analysis with adjustment for gestation and birthweight. Conclusions Hypertriglyceridemia is common in extremely preterm infants receiving parenteral lipid emulsions. Regular monitoring and prompt adjustment of lipid intake in the presence of hypertriglyceridemia, minimising the length of exposure to hypertriglyceridemia, may mitigate potential consequences.